Sosiolek Pekerja Seks Komersial Berstatus Mahasiswa di Lingkungan Kampus dan Lingkungan Prostitusi sebagai Representasi Status Sosial - Ratih Riana; S. Setiadi; E. D. Pratamanti (Jurnal Dinamika Sosial Budaya, 2017)
Every social group has their own sociolect which represent their specific intention. In order to understand its intention, whether or not it can really represent a particular social class, this research therefore purposed to explain the sociolect used by college students who is practising prostitution in their site and also in their college. The descriptions and analyses intended to discover the intention of respondents' sociolect as a mean of representation of their social status. The research data are obtained from the usage of sosiolect by female college students who are practising prostitution at the prostitution sites and at their college. Data collection techniques are using observations, recordings, and interview. Data analyses utilize qualitative methods. According to data analyses, respondents has their specific, unique and particular sosiolect at their prostitution sites and at their college. It is intended to make their communication easier with another prostitutes and their customer. In addition, their particular sociolect is used to protect their privation, the prostitutes and their customer, when they are out site. They employ both verbal and nonverbal sociolects. As the conclusion, their specific and unique sociolect is indeed a way to represent their social status and have specific intention understandable from their own standpoint.